Pengaruh Academic Burnout Terhadap Motivasi Belajar Siswa SMP Angkasa Lanud Padang - Nada Aisya Hasanah Bustami; Jingga Tsabitah; Icha Diana Putri; Nada Izdihar Firdausa; Adinda Fortuna; Izzanil Hidayati (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The role of education in shaping the quality of individuals and producing national intelligence is very important, especially at the junior high school level. However, at this level students often experience academic burnout, which is fatigue due to academic pressure that greatly affects their motivation to learn. The purpose of this study was to examine the effect of academic burnout on learning motivation in students of Angkasa Lanud Junior High School, Padang. The research data were collected using a Likert scale questionnaire completed by 30 students who were selected as samples from a total population of 58 students. Data analysis was carried out using the IBM SPSS version 20 application with the Spearman Rank Correlation non-parametric analysis technique. obtained r = 0.396 and p significance = 0.045. The results showed a significant influence between academic burnout and student learning motivation.